PERHITUNGAN VALUE AT RISK DENGAN PENDUGA VOLATILITAS STOKASTIK HESTON - DAMIYANTI, DESAK PUTU DEVI; DHARMAWAN, KOMANG; HARINI, LUH PUTU IDA (E-Jurnal Matematika; Vol 7 No 4 (2018), 2018)
Value at risk is a method that measures financial risk of an security or portfolio. The aims of the research is to find out the value at risk of an exchange rate using the Heston stochastic volatility model. Heston model is a strochastic volatility model that assumes that volatility of the security follow stochastic process and consider the mean reversion. Based on simulation result s , the value of volatility using Heston volatility estimastor is 0.2887, and the value of Heston VaR with 95 percent confident level is 0.0297. Based on result of backtesting ,  there are 48 violations obtained VaR using Heston model, while historical VaR there are 2 violations . Thus, VaR using Heston model is more strict in estimating risk.